Reducing Preoperative Anxiety: The Role of Anesthesia Provider Communication and Empathy - Ghazaly, Yusdi; Ahmad Jondris (Open Access Indonesian Journal of Medical Reviews, 2024)
Preoperative anxiety is a common and significant issue that can negatively impact patient outcomes. Effective communication and empathy from anesthesia providers have been suggested as crucial factors in mitigating this anxiety. This study aimed to investigate the relationship between anesthesia provider communication and empathy and preoperative anxiety levels in adult patients undergoing elective surgery. A prospective, observational study was conducted at a tertiary care hospital. Adult patients scheduled for elective surgery under general anesthesia were enrolled. Preoperative anxiety was assessed using the State-Trait Anxiety Inventory (STAI) before the anesthesia provider's preoperative visit and again immediately before surgery. Anesthesia provider communication and empathy were evaluated using the CARE (Communication Assessment Tool for Anesthesia Providers) questionnaire and the Jefferson Scale of Empathy (JSE), respectively. A total of 200 patients were included in the study. The mean preoperative anxiety score decreased significantly from before the anesthesia provider's visit to immediately before surgery (p < 0.001). Higher scores on the CARE questionnaire and the JSE were associated with a greater reduction in preoperative anxiety (p < 0.05). Multivariable analysis revealed that both effective communication and empathy independently contributed to reducing preoperative anxiety. Anesthesia provider communication and empathy play a crucial role in reducing preoperative anxiety. Implementing communication and empathy training programs for anesthesia providers may improve patient experiences and surgical outcomes.